Ficciones democráticas: un estudio sobre desigualdades sociales tornadas en asimetrías políticas- Libro de Gustavo Urbina - Luján, David (El Colegio de México, 2022)
In this review, a reading of the most recent book by Gustavo Urbina is offered, arguing about its most outstanding aspects and that give rise to reflect on issues of citizenship, power and participation. In addition, we explore some limitations of the text and lines of future research.